Human perception on thermal comfort of studio based classroom in northen region polytechnic / Mohamad Ibrahim Mohamed Noor - Mohamed Noor, Mohamad Ibrahim (Faculty of Architecture, Planning and Surveying, 2010)
Providing thermal comfort is the basic requirement of a building. In modem buildings this is usually accomplished with the help of mechanical cooling or heating. Ancient architecture, all over the world, had many characteristics which led to thermal comfort, i.e, the shape of the building and different parts of the building, (e.g. indoor spaces, doors, windows etc) were located and oriented to take maximum advantage of the climate. The role of trees, vegetation and water around the building in determining the thermal comfort was well appreciated. Therefore the objectives of this research are to know the comfort level in the studio classroom, to investigate the studio design to achieve the thermal comfort in Polytechnic and to outline and rank the most significant factors that influence thermal comfort in studio classrooms. The scope will cover the perception of thermal comfort level and the factor that affecting thermal comfort in the studio. To support this research, the structure interviews, observation and questionnaire form to collect the data. The analysis then will be decided upon suitability in the analysis process. The study indicated that human (studio users) perception on level of thermal comfort is good and the ventilation is the most significant factor to contribute the thermal comfort in the studio classrooms.